2005
DOI: 10.1038/sj.npp.1300841
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and Divergence in the Neurochemical Regulation of Prepulse Inhibition of Startle and N40 Suppression in Rats

Abstract: Prepulse inhibition of startle ('PPI'), a cross-species measure of sensorimotor gating, is impaired in schizophrenia patients. Suppression of P50 event-related potentials (ERPs) in response to the second of two clicks ('P50 gating') is also impaired in schizophrenia. Suppression of N40 ERPs to the second of two clicks ('N40 gating') is thought by some to be a rat homolog of human P50 gating. Emerging evidence suggests differences in the neurobiology of deficits detected by PPI vs P50 (or N40) gating. We record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 55 publications
11
45
1
Order By: Relevance
“…This supports the suggestion that while PPI and P50 do not share the same neural networks, they may share overlapping networks (Oranje et al, 2006) and hence it is possible that both serotonin and dopamine's modulation of PPI and P50 may be similar within critical areas of the overlapping network. These findings in general support observations in animals with equivalent measures on the neurochemical regulation of sensorimotor and sensory gating (Swerdlow et al, 2006).…”
Section: Combined Serotonin and Dopamine Depletionsupporting
confidence: 87%
“…This supports the suggestion that while PPI and P50 do not share the same neural networks, they may share overlapping networks (Oranje et al, 2006) and hence it is possible that both serotonin and dopamine's modulation of PPI and P50 may be similar within critical areas of the overlapping network. These findings in general support observations in animals with equivalent measures on the neurochemical regulation of sensorimotor and sensory gating (Swerdlow et al, 2006).…”
Section: Combined Serotonin and Dopamine Depletionsupporting
confidence: 87%
“…The lack of a correlation between PPI and auditory gating in the paired tone paradigm further corroborates evidence from human and animal studies that these paradigms measure two distinct mechanisms (Brenner et al, 2004;Ellenbroek et al, 1999;Swerdlow et al, 2006).…”
Section: Auditory Gatingsupporting
confidence: 75%
“…So far, most, but not all, studies in rats showed impairments of N40 -gating (the putative rat correlate of the human N100) with NMDAR blocking (Miller et al, 1992;de Bruin et al, 1999;Swerdlow et al, 2006). However, no effect of NMDAR antagonists on auditory gating was observed in a study in mice (Connolly et al, 2004).…”
Section: Auditory Gatingmentioning
confidence: 99%
“…The primary focus of this study was to investigate interactions between 5-HTT genotype, prenatal stress, and postnatal adversity and their interaction on hippocampal glucocorticoid receptor (GR) expression, the HPA stress response, and behaviors, all known to be influenced by early adversity and/or by the 5-HT system, including startle responses, PPI (Borrell, Vela, Arevalo-Martin, Molina-Holgado, & Guaza, 2002;Farid, Martinez, Geyer, & Swerdlow, 2000;Lovic & Fleming, 2004;Swerdlow et al, 2006), and locomotor activity in rats (Burton et al, 2006).…”
mentioning
confidence: 99%